Evaluation of Facial Beauty Using Anthropometric Proportions. (20th February 2014) - Milutinovic, Jovana; Zelic, Ksenija; Nedeljkovic, Nenad
Abstract : The improvement of a patient's facial appearance is one of the main goals of contemporary orthodontic treatment. The aim of this investigation was to evaluate the difference in facial proportions between attractive and anonymous females in order to establish objective facial features which are widely considered as beautiful. The study included two groups: first group consisted of 83 Caucasian female subjects between 22 and 28 years of age who were selected from the population of students at the University of Belgrade, and the second group included 24 attractive celebrity Caucasian females. The en face facial photographs were taken in natural head position (NHP). Numerous parameters were recorded on these photographs, in order to establish facial symmetry and correlation with the ideal set of proportions. This study showed significant difference between anonymous and attractive females. Attractive females showed smaller face in general and uniformity of the facial thirds and fifths, and most of the facial parameters meet the criteria of the ideal proportions.